Simulation and optimisation of an astrophotonic reformatter - Anagnos, Theodoros; Harris, Robert J.; Quirrenbach, Andreas (Monthly notices of the Royal Astronomical Society, 2018)
ABSTRACT. Image slicing is a powerful technique in astronomy. It allows the instrument designer to reduce the slit width of the spectrograph, increasing spectr